SnO(2)/TiO(2) Thin Film n-n Heterostructures of Improved Sensitivity to NO(2) - Nowak, Piotr (Sensors (Basel), 2020)
Thin-film n-n nanoheterostructures of SnO(2)/TiO(2), highly sensitive to NO(2), were obtained in a two-step process: (i) magnetron sputtering, MS followed by (ii) Langmuir-Blodgett, L–B, technique. Thick (200 nm) SnO(2) base layers were deposited by MS and subsequently overcoated with a thin and discontinuous TiO(2) film by means of L–B. Rutile nanopowder spread over the ethanol/chloroform/water formed a suspension, which was used as a source in L–B method. The morphology, crystallographic and electronic properties of the prepared sensors were studied by scanning electron microscopy, SEM, X-ray diffraction, XRD in glancing incidence geometry, GID, X-ray photoemission spectroscopy, XPS, and uv-vis-nir spectrophotometry, respectively. It was found that amorphous SnO(2) films responded to relatively low concentrations of NO(2) of about 200 ppb. A change of more than two orders of magnitude in the electrical resistivity upon exposure to NO(2) was further enhanced in SnO(2)/TiO(2) n-n nanoheterostructures. The best sensor responses R(NO2)/R(0) were obtained at the lowest operating temperatures of about 120 °C, which is typical for nanomaterials. Response (recovery) times to 400 ppb NO(2) were determined as a function of the operating temperature and indicated a significant decrease from 62 (42) s at 123 °C to 12 (19) s at 385 °C A much smaller sensitivity to H(2) was observed, which might be advantageous for selective detection of nitrogen oxides. The influence of humidity on the NO(2) response was demonstrated to be significantly below 150 °C and systematically decreased upon increase in the operating temperature up to 400 °C.